Advanced engineering mathematics - Stroud, K.A.; Booth, Dexter J. (London, United Kingdom : Red Globe Press, 2020)
A long-standing, best-selling, comprehensive textbook covering all the mathematics required on upper level engineering mathematics undergraduate courses. Its unique approach takes you through all the mathematics you need in a step-by-step fashion with a wealth of examples and exercises. The text demands that you engage with it by asking you to complete steps that you should be able to manage from previous examples or knowledge you have acquired, while carefully introducing new steps. By working with the authors through the examples, you become proficient as you go. By the time you come to trying examples on their own, confidence is high.
Hints on Using the Book Useful Background Information Numerical Solutions of Equations and Interpolation Laplace Transforms -- Part 1 Laplace Transforms -- Part 2 Laplace Transforms -- Part 3 Difference Equations and the Z Transform Introduction to Invariant Linear Systems Fourier Series -- 1 Fourier Series -- 2 Introduction to the Fourier Transform Power Series Solutions of Ordinary Differential Equations -- 1 Power Series Solutions of Ordinary Differential Equations -- 2 Power Series Solutions of Ordinary Differential Equations -- 3 Numerical Solutions of Ordinary Differential Equations Matrix Algebra Systems of Ordinary Differential Equations Direction Fields Phase Plane Analysis Non-linear Systems Dynamical Systems Partial Differentiation Partial Differential Equations Numerical Solutions of Partial Differential Equations Multiple Integration -- Part 1 Multiple Integration -- Part 2 Integral Functions Vector Analysis -- Part 1 Vector Analysis -- Part 2 Vector Analysis -- Part 3 Complex Analysis -- Part 1 Complex Analysis -- Part 2 Complex Analysis -- Part 3 Optimization and Linear Programming.
Includes index.
Keywords: ENGINEERING MATHEMATICS